A study to evaluate the effectiveness of using anaglyph 3D glasses for pain management during the Inferior alveolar nerve block of pediatric patients (A Randomized Controlled Clinical Trial) (Journal of Hama University, 2022)
Aims and objectives: The aim of this study was to evaluate the efficiency of using 3D anaglyph glasses as an audiovisual distraction method for pain management during the Inferior alveolar nerve block of pediatric patients.Materials and methods: The study was designed as a randomized controlled clinical trial, 44 potentially cooperative children between the ages of 4-10 years (both males and females) were elected to participate in this study and were divided into two groups, 4 patients were excluded 1st group: 20 patients were treated by using conventional behavioral management techniques during IANB, 2nd group: 20 patients were treated by using Anaglyph 3D polarized Glasses as an audiovisual distraction technique during IANB. Pain levels were evaluated by two behavioral pain scales, the first scale was Wong-Baker Faces Pain Rating Scale (a Self-Reported Scale), and the second scale was the pulse oximetry scale (a physiological scale). Results: After conducting Mann -Whitney U Test and in the SPSS 20 statistics software on Wong-Baker faces pain rating scale the results were a higher average of ranks in the 1st group with statistically significant differences (P